2015
DOI: 10.5551/jat.29926
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Artery Calcium Score Compared with Cardio-Ankle Vascular Index in the Prediction of Cardiovascular Events in Asymptomatic Patients with Type 2 Diabetes

Abstract: Aim: Coronary artery calcium (CAC) score has a role in stratifying cardiovascular risk in patients with diabetes. Cardio-ankle vascular index (CAVI) is also a useful method to detect coronary artery calcification. This study compares CAC score with CAVI in the prediction of cardiovascular events in patients with diabetes. Methods: From August 2006 to June 2008, a total of 626 patients with diabetes who received CAC score assessment with concomitant tests of ankle-brachial index and CAVI were included in this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
47
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(54 citation statements)
references
References 48 publications
5
47
0
2
Order By: Relevance
“…Although CAC score has a greater predictive value, CAVI seems also a useful method for the risk stratification of asymptomatic type 2 diabetic patients. Importantly, CAVI presents a range of advantages, such as being a low-cost procedure, is easy to be calculated and is not affected by blood pressure (37).…”
Section: Imaging Methods As Predictors For Cadmentioning
confidence: 99%
“…Although CAC score has a greater predictive value, CAVI seems also a useful method for the risk stratification of asymptomatic type 2 diabetic patients. Importantly, CAVI presents a range of advantages, such as being a low-cost procedure, is easy to be calculated and is not affected by blood pressure (37).…”
Section: Imaging Methods As Predictors For Cadmentioning
confidence: 99%
“…In the clinical setting, the coronary artery calcium score, the cardio-ankle vascular index, and pulse wave velocity are screening tools to detect coronary artery calcification and arterial sclerosis 13, 14) . Clinical factors associated with arterial stenosis (AS) are similar to risk factors for VC 15) .…”
Section: Introductionmentioning
confidence: 99%
“…These levels seemed to be too high for the cutoff level of CAVI. Chung et al [9] showed that patients with CAVI > 9.0 had a greater incidence of cardiovascular events than those with CAVI ≤9.0 (HR 1.18, p = 0.049) in diabetes patients, and Sato et al [10] showed that higher CAVI (CAVI ≥10.09) had greater cardiovascular events in metabolic syndrome patients. Kubota et al [11] showed that high CAVI (CAVI ≥10) posed a higher risk of cardiovascular disease events than low CAVI (CAVI < 9) did, and thus further discussion about appropriate cutoff values for discriminating low and medium risk will be needed.…”
Section: Assessment Of the Cutoff Level In Cavimentioning
confidence: 99%